If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3b + 4 = -7b + 11 Reorder the terms: 4 + 3b = -7b + 11 Reorder the terms: 4 + 3b = 11 + -7b Solving 4 + 3b = 11 + -7b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '7b' to each side of the equation. 4 + 3b + 7b = 11 + -7b + 7b Combine like terms: 3b + 7b = 10b 4 + 10b = 11 + -7b + 7b Combine like terms: -7b + 7b = 0 4 + 10b = 11 + 0 4 + 10b = 11 Add '-4' to each side of the equation. 4 + -4 + 10b = 11 + -4 Combine like terms: 4 + -4 = 0 0 + 10b = 11 + -4 10b = 11 + -4 Combine like terms: 11 + -4 = 7 10b = 7 Divide each side by '10'. b = 0.7 Simplifying b = 0.7
| 7a-3b=1 | | Q=180-5p | | 9x-3+8x=2x+4-4x | | f(x)=5x^4+12x^3+-16x^2+10 | | 6.5w=-123.5 | | 9x-7x=36 | | -2x-2=50x-50 | | 6x+7x+9x=88 | | 10-3=x-9 | | R=F+460 | | 2x+y=1.25 | | 5x+2x=154 | | 6x+(-78)-30x=-6 | | 2x-8x+3x-7x= | | 15-7w=1 | | y=-1.4x+4.25 | | 3x^3+22x=0 | | 2x+8x+3x-7x= | | 2x-8x-3x-7x= | | 3(X-6)+5=8 | | 2x+8x-3x-7x= | | -b+6b=b+1+5b | | -3t+16=10 | | f(x)=5x^4+15x^2+10 | | 79+k=84 | | 9x+x=70+8x | | 7=5v-3 | | -15(x-c)=15 | | N^2+20n-40=-9 | | -3+16=10 | | y-1=-6(x+2) | | 9a+5b=1 |